CLINICAL AND PHARMACOKINETIC EQUIVALENCE OF ORIGINAL AND GENERIC AMLODIPINE IN PATIENTS WITH MILD-TO-MODERATE ARTERIAL HYPERTENSION - N. A. Belolipetskiy; S. N. Tolpygina; J. B. Zverkov; V. V. Pisarev; I. E. Koltunov; V. G. Belolipetskaya; S. J. Martsevich (Столичная издательская компания, 2015)
Aim. To study clinical equivalence of two amlodipines under the control of their plasma levels and evaluate their pharmacoeconomical efficacy in patients with arterial hypertension (AH).Material and methods. 31 patient with AH were included in the study (14 men and 17 women). 21 (66 %) patients had AH of 1 stage and 10 (34 %) patients had AH of 2 stage. All patients were 39-81 y.o. (average - 60 y.o.) with AH duration 0,5-43 years (average - 17,9 years). Antihypertensive effect of Amlorus (Synthesis, Russia) and Norvasc (Pfizer, USA) was evaluated in the study. Blood pressure (BP), amlodipine plasma levels (by liquid chromatography with mass spectrometry) and side effects were registered before and after 2, 4 and 6 weeks of therapy. Hydrochlorothiazide 25 mg/d was added if the monotherapy with amlodipine10 mg/d had not been efficient. Therapy with the second studied amlodipine followed the therapy with the first drug.Results. Both drugs provided similar plasma amlodipine concentrations with significant BP reduction. 96,6 % and 90 % of patients reached BP target level (<140/90 mm Hg) after 6 weeks of Amlorus and Norvasc therapy, respectively. Hydrochlorothiazide was needed in 23,3 % and 26,7 % of patients taking Amlorus and Norvasc, respectively. Cost of Amlorus therapy per patient was 221 rbl/month in comparison with cost of 727 rbl/month for Norvasc therapy.Conclusion. Generic Amlorus showed clinical and pharmacokinetic equivalency with an original amlodipine Norvasc and lower cost of therapy.